GENDER REPRESENTATION IN LANGUAGE TEXTBOOKS: A CRITICAL ANALYSIS - Kristiyawan, Firda Agus; Rarasati, Ida Putri (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
The representation of gender in educational materials, particularly textbooks, has been a subject of ongoing research and discussion. Research indicates that these materials often reflect and perpetuate societal norms and biases, which can significantly influence students' perceptions of gender roles and identities. This concern is particularly relevant in language textbooks, where the portrayal of characters and scenarios can shape young learners' understanding of gender dynamics and contribute to either the reinforcement or challenge of existing stereotypes. By adopting a critical lens, educators and policymakers can work towards creating more inclusive and empowering educational resources that foster gender equity and social justice within the classroom and beyond. The analysis of the textbook images revealed a stark gender imbalance, with male characters featured significantly more often than female characters and often depicted in positions of authority, leadership, and high-status occupations, while female characters were frequently shown in domestic or supportive roles.